Planning, Implementing and Evaluating in Sports Coaching - Vlad I. ROȘCA (Revista de Management Comparat International)
Achieving success in sports is strongly related to peaking at the right intervals. Peaking means that athletes are able to deliver their best performances at a certain given time of competition. This paper looks at the attributions of coaches in such a high standard preparation, arguing that, if reaching sporting success is the end goal, then the preparation of athletes needs to mean more than the simple training of motorical skills. The importance and necessity of adopting the managerial principles of planning, implementing and evaluating in sports coaching are being discussed. The research aim is to detail on how a managerial like-approach can be beneficial for coaching. Sports-specific characteristics of planning, implementing and evaluating are discussed in detail.